Assessment of shoulder pain and somatic dysfunction in young competitive swimmers: Preventive Osteopathic Manipulative Treatment - Granger, Fanny; Etevenard, Marion; Kily, Jean-Pascal; Garet, Martin (Journal of Sports Medicine and Therapy, 2019)
Context: Shoulder pain is one of the most frequent reported complaints in intensive competitive swimming. The so-called ‘swimmers’ shoulder’ has been widely explored and has been reported sometimes without specific reference to contributing mechanisms or structures. Somatic dysfunction is defined as an impaired or altered function of related components of the somatic system and may appear in the early stage of pain feeling. Aim: To evaluate somatic dysfunctions in a group of young competitive swimmers with and without shoulder pain and its relationship with the shoulder’s mobility along with the efficacy of an osteopathic manipulative treatment (OMT) on shoulder’s mobility, pain, and comfort of swimming. Material and method: 20 competitive swimmers (14.6 ± 1.3 ys; 11.6 ± 2.4 hs.wk-1) were divided into two groups, with and without shoulder pain (SPG/CG). Before and after light touch/OMT, and 1 week later, somatic dysfunctions, shoulder’s range of mobility, pain, and swimming comfort were assessed by 2 independent osteopaths. Results: Somatic dysfunctions were observed in both groups without significant differences in the number or localization and were independent of severity of pain. In the SPG, pain decreased significantly after OMT (6.1 ± 1.9 vs. 3.9 ± 1.8; p = 0.001) and remained stable 1-week later (P = NS). Shoulder’s mobility was lower on the aching shoulder in the “shoulder pain” group when compared to the control group on flexion and abduction tests but not on extension or adduction tests. Following OMT, only abduction improved when compared to light touch. Comfort in swimming was reported as “better” in both OMT/light touch groups. Conclusion: There is no difference between light touch and OMT as both decreased pain and increased comfort in swimming but abduction range of motion only improved in the OMT group.